مدى فاعلية التدريب في تطوير الموارد البشرية في المديرية العامة للتربية والتعليم بمحافظة الظاهرة الظاهرة بسلطنة عمان من وجهة نظر المعلمين - فهد بن حمد بن سليم الصوافي
This research aims to answer many questions raised about the effectiveness of training in the Directorate General of Education in Al Dhahira Governorate from teachers' point of view, and if the relationship between the effectiveness of training by determining the training needs, planning, implementation and evaluation. As well as whether there are statistical differences due to the variables (type, academic qualifications, years of experience, courses' numbers) to judge the effectiveness of the training from teachers' point of view. The researcher followed the descriptive analytical method for the collection of texts and articles related to the topic. Questionnaire was also used as a tool for the study. It consisted of (47) items distributed on the axes of the training process and they were analyzed using the statistical analysis software SPSS. The research came up with several results and the most important ones are the results which achieve the main aim of the research which is the training programs implemented in the Directorate General of Education in Al Dhahira Governorate have medium efficiency and positive impact. Also there is a statistical significance connects between the effectiveness of training and training areas which is positive relationship (proportional). The results also showed that the effectiveness of the training is not affected by; the gender (males and females), the academic qualifications and the number of courses the teacher attended. That means there are no statistically significant differences. In addition, the results showed statistically significant differences between the effectiveness of training and years of experience. The study also found that the training offered by the training center in Al Dhahira Governorate will help to improve the trainee's performance. The contribution of the current study is being a route map for; paying more attention to the quality of training, activating the role of those in charge of training management in understanding the center of training process, focusing on the identifying training needs and planning for training, linking training with the annual evaluation of the teacher, increasing training support financially and morally, and creating a database for training as a system to get information and reports.